Work-Life Balance as a Key to Enhancing Employee Performance: An Analysis of the Mediating Role between Motivation and Work Stress at Bank Muamalat East Java Regional Office - Monika Fatmasari; Mardany, Ronny Malavia; Basalamah, Muhammad Ridwan (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the mediating role of work-life balance in the relationship between motivation, work stress, and employee performance at Bank Muamalat Regional East Java. Optimal employee performance is significantly influenced by psychological factors such as motivation and work stress, as well as the individual's ability to balance work and personal life (work-life balance). The research method used is a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 105 respondents who are employees from several Bank Muamalat branch offices in East Java. Data analysis was conducted using Structural Equation Modeling (SEM) with AMOS software. The results of the study indicate that motivation does not have a positive effect on work-life balance and employee performance, while work stress has a negative effect on both work-life balance and performance. Work stress was found to significantly affect work-life balance, but it does not significantly influence employee performance, either directly or through the mediation of work-life balance. Moreover, work-life balance itself was also found to have no significant effect on employee performance.